Catheter Ablation of Ventricular Arrhythmias Originating From the Pulmonary Sinus Cusp in Pediatric Patients: A Single-Center Retrospective Study - Liu, Tian; Liang, Dongpo; Liao, Zili; Zhang, Zhiwei; Wang, Shushui; Zeng, Shaoying (Frontiers in Pediatrics, 2019)
Objective: There are scarce reports on ventricular arrhythmias (VAs) originating from the pulmonary sinus cusp (PSC) in pediatric patients. We investigated to ablate PSC-VAs in pediatric patients. Study design: Clinical, echocardiographic, and ablation data were reviewed in 10 consecutive symptomatic children who underwent successful ablation of VAs of PSC origin at our center between March 2014 and June 2018. Results: The 10 patients, weight ranged from 29 to 63.5 kg; had structurally normal hearts and VAs with left bundle branch block morphology and inferior axis. The initial ablation was performed in the right ventricular outflow tract (RVOT) or the aortic sinus cusp and failed to terminate the VAs in 9 patients. The successful ablation site was in the right cusp (RC) in 7 patients, the anterior cusp in 2, the left cusp (LC) in 1. The earliest potential recorded at the PSC ablation site preceded the onset of QRS complex during VAs by 29.4±4.9ms. Conclusions VAs with left bundle branch block morphology and inferior axis may originate within the PSC in children. Because of the particularity of ablation in pediatric patients, mapping in the PSC should be considered when failed ablation in the RVOT.